2023
DOI: 10.1111/jcpp.13815
|View full text |Cite
|
Sign up to set email alerts
|

Academic motivation decreases across adolescence for youth with and without attention‐deficit/hyperactivity disorder: Effects of motivation on academic success

Abstract: Background This longitudinal study examined growth trajectories of academic motivation in youth with and without attention‐deficit/hyperactivity disorder (ADHD) across the important developmental transition from middle school to high school, and associations with academic success. Consistent with self‐determination theory (SDT) of motivation, trajectories of amotivation, extrinsic motivation, and intrinsic motivation were modeled. Methods The study included a robust multi‐method, multi‐source assessment of aca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Regarding these influencing factors, we can categorize them into two main aspects: internal factors within the students themselves and external factors that surround the students. For instance, Smith et al (2023) conducted a study with 302 adolescent participants and found that teenagers with attention deficit or hyperactivity disorders generally exhibit lower levels of learning motivation, which in turn affects their academic performance. The internal factors such as sleep (Boraita et al, 2023;Chan et al, 2023;Hamvai et al, 2023), depression (Song et al, 2023;Urbanska-Grosz et al, 2023), and disordered social media use (Almarzouki et al, 2022;Sserunkuuma et al, 2023) also exert varying degrees of influence on academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding these influencing factors, we can categorize them into two main aspects: internal factors within the students themselves and external factors that surround the students. For instance, Smith et al (2023) conducted a study with 302 adolescent participants and found that teenagers with attention deficit or hyperactivity disorders generally exhibit lower levels of learning motivation, which in turn affects their academic performance. The internal factors such as sleep (Boraita et al, 2023;Chan et al, 2023;Hamvai et al, 2023), depression (Song et al, 2023;Urbanska-Grosz et al, 2023), and disordered social media use (Almarzouki et al, 2022;Sserunkuuma et al, 2023) also exert varying degrees of influence on academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding these influencing factors, we can categorize them into two main aspects: internal factors within the students themselves and external factors that surround the students. For instance, Smith et al (2023) conducted a study with 302 adolescent participants and found that teenagers with attention deficit or hyperactivity disorders generally exhibit lower levels of learning motivation, which in turn affects their academic performance. The internal factors such as sleep (Boraita et al, 2023;Hamvai et al, 2023), depression (Song et al, 2023;Urbanska-Grosz et al, 2023), and disordered social media use (Almarzouki et al, 2022;Sserunkuuma et al, 2023) also exert varying degrees of influence on academic performance.…”
Section: Introductionmentioning
confidence: 99%